Perancangan dan Implementasi Gerakan Senam Melalui Alat Musik Dambus Khas Bangka Belitung - Sinta Naviri; Yorenza Meifinda (CENDEKIAWAN, 2026)
The aim of this research is to recognize and foster a sense of love for local culture, the dambus musical instrument which is typical of Bangka Belitung combined with gymnastic movements to create harmonious gymnastic movements that fulfill cultural values. The research method in this study is descriptive qualitative, data collection techniques using observation, interviews and questionnaires, data analysis techniques using data triangulation, conclusions on research on the implementation of gymnastic movements using the dambus musical instrument are carried out in several stages including, The first stage is by recognizing the musical instrument dambus which is a Bangka Belitung culture, then the second stage is recognizing the basic movements of gymnastics, the third stage is introducing complex movements accompanied by the sound of the dambus musical instrument, the fourth stage is repetition of basic movements and movements complicated, and the final stage is strengthening the movements accompanied by the dambus musical instrument.